PEMBANGUNAN WEB SITE PROGRAM STUDI ILMU ADMINISTRASI BISNIS SEBAGAI MEDIA PROMOSI KEPADA MASYARAKAT - Adi Wijaya Putra; Dahlan Susilo; Astri Charolina (Universitas Sahid Surakarta, 2017)
Sahid Surakarta University (USS) is a private university education institution in Surakarta which located at AdiSucipto street No. 154 Jajar, Surakarta. USS has several study programs, one of them is business administration, this study program has been had a company profile as information system, the weakness of this system was the lack of information, one of the solutions to minimize the weakness is by making a website. The purpose of this study was produce a website to inform about Business Administration Study Program. In this study, the website used observation, interview, literature, and software development. It also used PHP (Pear Hypertext Prepocessor) in the programming and used CI (Code Eghniterl) in its framework, MySQL as its database server and to support the programming was also used software such as Notepad ++ and Macromedia Dreamweaver.The business administration study program’s wibsite was tested by using webqual method, this test obtained 30 respondents that got positive responses between usability to the visitors by generating the value of 0.080, and also got positive results between the information quality to the visitors with value of 0.271, and also got positive results between the interactions quality to visitors with a value of 0.648.